A Prosopographical Research of Itinerant Religious People in the Late Antique Mediterranean: Preliminary Results - Gritti, Elena (ARYS. Antigüedad: Religiones y Sociedades, 2025)
Already in Antiquity, but even more so in Late Antiquity, there was an intense phase of mobility and transformation of societies; by focusing on a good number of prosopographical data, it is possible to illustrate, at least partially, the historical evolutionary process of the Mediterranean area itself in its religious context. Between the 4th and 6th centuries CE, the ecclesiastical component (pilgrimages and itinerant sanctity) predominates in the Mediterranean. In most cases, religious people travelled because they were involved in embassies, which involved long and arduous journeys between the most important political and religious power places in the empire (in primis sedes regiae). Some of them aspired to advance their careers, others only wanted to reach loca sancta out of devotion and to meet prominent personalities of the Mediterranean religious scene (think of the attraction of personalities such as Bishop Basil in Caesarea Cappadocia or Jerome in Bethlehem). The movements are also fuelled by the circulation of relics, which received a particular impetus from the second half of the 4th century onwards, and if not pilgrimages, the migrations of saints and saintly figures are quite frequent; hagiographies often include narratives of sporadic journeys by sea and land. My paper will focus on a few representative cases of a larger prosopographical study that has not yet been published, to investigate above all the purposes of religious mobility, the categories of individuals most involved (considering also the female component), the means used for the journeys, the most travelled itineraries and thus the calendar and organisation established for undertaking journeys, missions or the like. Some case studies are presented below: Germanus presbyter; Abraham abbas; Iulia Eustochio y Rusticiana; Iovinianus monachus; Iohannes defensor; Bassus presbyter.
Keywords: Religious Mobility; Diplomacy; Letters; Evergetism